Proposal of an empirical model to estimate the productivity of ‘Valencia’ orange (Citrus sinensis L. Osbeck) in the Colombian low tropics (2021)
The response of the citrus crop to environmental supply largely determines the speed and intensity of the plant's ecophysiological processes, which affect the development and production of the crop. The main objective was to analyze the effects of climatic conditions on the productivity of the ‘Valencia’ orange agroecosystems (Citrus sinensis L. Osbeck) previously typified in the department of Meta, Colombia. The climatological variables precipitation (PPT), maximum and minimum temperatures (Tmax and Tmin), wind speed, relative humidity and solar brightness were analyzed in an observation window spanning the years 2013 to 2015. Using the FAO CropWat model, the crop reference evapotranspiration (ETo) was obtained to applied agroclimatic indices. Using the statistical software STATGRAPHICS Centurion XVI v. 16.2.04, an empirical model was proposed that relates productivity according to agroclimatic indices, for the vegetative and reproductive phenological phases. It was found that the proposed empirical model explains 49% (P=0.0233) of the oscillation of productivity in study area agroecosystems. The model, based on agroclimatic indices associated with PPT, ETo, Tmax and Tmin, found that the relationship between productivity and agroclimatic indices is non-linear. It was established that productivity variation is mainly influenced by PPT, the occurrence and magnitude of which determines the volume of production and quality of the fruit. On the other hand, whereas increases in air temperature and the occurrence of water deficits in the pre-flowering and flowering phases positively favor crop production, the same factors produce a negative effect in the setting phase.